1997
DOI: 10.1192/apt.3.1.25
|View full text |Cite
|
Sign up to set email alerts
|

What a general practitioner can expect from a consultant psychiatrist

Abstract: There are many similarities in the experience and approach of general practitioners (GPs) and psychiatrists. GPs may spend some time in psychiatric posts before settling down as principals in their own practice, while some psychiatrists are members of both their own College and the Royal College of General Practitioners. Although there is great potential benefit for patients in this symbiotic relationship, GPs and psychiatrists work in different settings that require different techniques and time-scales. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The quality of psychiatric patient care is known to be partly dependent on communication between general practitioners (GPs) and psychiatrists (Wright, 1997). Many studies look at clinical letter quality (Pullen and Yellowlees, 1985; Williams and Wallace, 1974) but few focus on the pathways involved, in this communication.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of psychiatric patient care is known to be partly dependent on communication between general practitioners (GPs) and psychiatrists (Wright, 1997). Many studies look at clinical letter quality (Pullen and Yellowlees, 1985; Williams and Wallace, 1974) but few focus on the pathways involved, in this communication.…”
Section: Introductionmentioning
confidence: 99%
“…GPs expect mental health services to be accessible. Wright (1997) has outlined the problems that GPs perceive with services: these include the geographical remoteness of mental health hospitals, poor communication, lack of clarity about management, long waiting lists, problems with urgent referrals, too little contact with other mental health professionals (e.g. CPNs, psychologists) and too few patients discharged back to general practice care.…”
Section: Why Work With Primary Care?mentioning
confidence: 99%
“…Studies have shown that there are considerable inequalities in the distribution of resources in primary care.The employment of more community psychiatric nurses, learning disability nurses and primary care facilitators to work closely with primary care services, while remaining members of community mental health/learning disability teams, may be a solution (Wright, 1997).The Royal College of Nursing (1994) has suggested that community learning disability nurses could be part of primary care teams.…”
Section: Boxmentioning
confidence: 99%